Real‐world effectiveness of fulvestrant monotherapy as first endocrine treatment in patients with metastatic breast cancer. Issue 2 (17th September 2019) - Skinner, Karen E.; Olufade, Temitope; Walker, Mark S.; Schwartzberg, Lee S.
Abstract: Fulvestrant monotherapy is approved for postmenopausal women with hormone receptor‐positive, metastatic breast cancer (MBC) who progressed following antiendocrine therapy, or those with hormone receptor‐positive, human epidermal receptor 2‐negative advanced breast cancer (BC) not previously treated with endocrine therapy (ET). However, real‐world data are lacking. Retrospective reviews of 10 United States community oncology practices identified patients diagnosed with MBC between 1 January 2011 and 31 December 2015 who received fulvestrant as the first ET, either as initial therapy for metastatic disease or after progression following one line of chemotherapy. Endpoints were progression‐free survival (PFS) and overall survival (OS). Patients were classified as ET‐naïve or by relapse status following adjuvant ET ("early" recurrence during or ≤12 months of completing adjuvant ET, or "late" >12 months after completing adjuvant ET). Outcomes were evaluated using Kaplan‐Meier methods. Among 121 patients, median PFS (95% confidence interval) was 8.3 months (4.8‐12.3) for early relapse, 15.4 months (10.2‐21.2) for late relapse, and 18.7 months (10.1‐20.8) among ET‐naïve patients ( P  = .018). Median OS was 39.8 months (25.0‐55.1) for early relapse and 61.4 months (47.1‐61.4) for late relapse, but was not reached (NR; 55.6–NR) for ET‐naïve patients ( P  = .002). Fulvestrant monotherapy as the first ET after MBC diagnosis demonstrates PFS comparable to clinical study results; outcomes appeared better in patients without prior ET exposure and in patients with disease recurrence >12 months following adjuvant ET. These findings support fulvestrant monotherapy in patients with hormone receptor‐positive MBC.